การประมาณแรงตึงผิวของน้ำมันพืชด้วยกฎควบรวมพลังงานอิสระ: Estimating the Surface Tension of Vegetable oils by Law of Free Energy Additivity - Phankosol, Suriya; Chum-in, Thinnaphop; Krisnangkura, Kanit (Asian Health, Science and Technology Reports, 2016)
แรงตึงผิวเป็นสมบัติทางกายภาพที่สำคัญของของเหลวโดยเป็นตัวกำหนดขนาดของละอองจากหัวฉีดและการเผาไหม้ในกระบอกสูบ งานวิจัยนี้สนใจการประมาณแรงตึงผิวของน้ำมันพืชจากกฎควบรวมพลังงานอิสระของมาร์ติน (Martin’s rule of free energy additivity) ซึ่งคลอบคลุมถึงพลังงานอิสระของปฏิสัมพันธ์ระหว่างผิว (Free energy of interfacial interaction) สมการที่นำเสนอสามารถประมาณแรงตึงผิวของน้ำมันพืชได้จาก 2 วิธี คือ 1) จำนวนอะตอมคาร์บอนเฉลี่ย ( ) จำนวนพันธะคู่เฉลี่ย ( ) หรือ 2) ค่าสะปอน นิฟิเคชัน (SN) และค่าไอโอดีน (IV) ในการศึกษาใช้ข้อมูลจากเอกสารอ้างอิงมาใช้ในการศึกษาและสนับสนุนเพื่อยืนยันความถูกต้องแม่นยำของสมการที่จะนำไปใช้ สมการที่นำเสนอง่ายต่อการใช้งานและมีความถูกต้องแม่นยำในการประมาณแรงตึงผิวของน้ำมันพืชที่อุณหภูมิต่างๆ เทียบกับข้อมูลจากเอกสารอ้างอิง โดยทั้ง 2 วิธีมีความแม่นยำเท่ากัน โดยค่าความคลาดเคลื่อนสัมบูรณ์เฉลี่ยและค่าความคลาดเคลื่อนมาตรฐานที่ช่วงอุณหภูมิ 10-140oC เท่ากับ 0.33% และ 0.120 ตามลำดับ (80 ข้อมูล) การใช้สมการทำนายแรงตึงผิวนอกช่วงอุณหภูมิที่นำเสนออาจทำให้ความแม่นยำต่ำลง Surface tension is an important physical property of liquid. It dictates atomization of the fuel injector and combustion in the combustion chamber. In this work, an empirical approach for estimation surface tension of vegetable oils from the Martin’s rule of free energy additivity is extended to cover free energy of interfacial interaction. เป็น The proposed equations can estimate the surface tension of vegetable oils from either 1) its average carbon number of atoms ( ) and number of double bonds average ( ) or 2) its saponification number (SN) and iodine value (IV). Data available in literatures are used to validate, and support the speculations derived from the proposed equation. The proposed equations are easy to use and the estimated surface tension values of vegetable oils at different temperatures agree well with the literature values by both equations. The average absolute deviation (AAD (%)) and standard error of estimated at 10-140oC are 0.33% and 0.120, respectively (80 data points). Using the propose equation beyond this presented temperature range may possibly make lower accuracy.